Gambaran Penggunaan Antibiotik Profilaksis Pada Penderita Yang Menjalani Sectio Caesarea Di Beberapa Rumah Sakit Di Wilayah Indonesia Periode Tahun 2010 Sampai Dengan Tahun 2020 - Tauriangke, Andi Khiswah Nur; Rauf, Darmawati; Syamsuddin, Fatmawati Annisa (Fakultas Kedokteran Universitas Bosowa, 2025)
Prophylactic antibiotics are antibiotics given 30 minutes – 1 hour before a medical procedure that aims to keep the surgical wound from becoming infected. In Indonesia, about 44% – 97% use prescription antibiotics, although often not according to indications. One indication of the use of prophylactic antibiotics is infection that can appear in postoperative patients. This research is descriptive with a cross sectional approach. The study was conducted by collecting several journals regarding the description of the use of prophylactic antibiotics in patients undergoing Sectio Caesarea in several hospitals in Indonesia for the period 2010 to 2020. The subject of the study was a journal about the description of the use of prophylactic antibiotics in patients undergoing Sectio Caesarea in several homes. sick in the territory of Indonesia for the period 2010 to 2020. The sampling technique used is non-probability sampling. Data collection in this study used all data on patients who underwent Sectio caesarea and used antibiotics obtained from several journals and entered into Microsoft Excel. Obtained data on the age distribution of patients with Sectio Caesarea as many as 915 patients. Which consisted of 698 patients (76.28%) under 35 years and 217 patients (23.71%) over 35 years. There are 20 indications for Sectio Caesarea, dominated by Premature Rupture of membranes as many as 141 patients (21.82%) and the least is hydrocephalus as many as 1 patient (0.15%). The number of appropriate use of prophylactic antibiotics was 109 patients (9.62%) while the inappropriate use was 1,024 patients (90.37%). Based on the correct time of administration, 1,350 patients (95.27%) and the inappropriately amounted to 67 patients (4.72%). showed the correct dose of prophylactic antibiotics was 926 patients (79.69%) and incorrectly 236 patients (20.30%). In this study, it was found that the suitability of the use of prophylactic antibiotics in several hospitals with the Regulation of the Minister of Health of the Republic of Indonesia Number 2406/MENKES/PER/XII/2016 concerning general guidelines for the use of antibiotics was not in accordance with the guidelines covering aspects of the type of prophylactic antibiotics and according to the guidelines covering aspects of time. administration and dosage